Patient-reported outcome measures in orthodontics - Elbe Peter; R M Baiju; Jolly Mary Varughese; N O Varghese (Wolters Kluwer Medknow Publications, 2019)
Psychological perspective of orthodontic patients due to malocclusion and treatment is less explored in orthodontics until recently. Use of psychometric tools is the method to measure this intangible dimension of malocclusion and treatment. However, many generic and condition-specific tools are available now for this purpose. Patient-reported outcome measures (PROMs) will supplement normative outcome measures in the future and will remain an important aspect in patient-centered orthodontic care. In general, with the use of these tools, there has been a conflicting report regarding the effect of malocclusion on a person's Oral Health-Related Quality of Life (OHRQoL). However, orthodontic treatment has shown consistently to improve OHRQoL though there is a transient worsening in the initial phases of treatment. The effect of self-esteem and psychosocial well-being as mediators influencing OHRQoL and contextual factors such as socioeconomic status and family support mechanism on QoL need further evidence from long-term studies.